Modified carbon aerogel material, modified polypropylene composite material and preparation methods of modified carbon aerogel material and modified polypropylene composite material

By preparing a modified carbon aerogel material with a surface loaded FeOOH and adding it to polypropylene to form a modified polypropylene composite material, the problem of the lack of electromagnetic shielding performance of existing polypropylene materials is solved, and the efficient electromagnetic shielding effect of polypropylene materials is achieved.

CN119798786APending Publication Date: 2025-04-11HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954260.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing polypropylene materials lack electromagnetic shielding performance and are difficult to effectively apply in electronic equipment, communication equipment, medical equipment, building materials, automobiles and other fields.

Method used

By preparing a modified carbon aerogel material with a surface loaded FeOOH, it is added to polypropylene as an electromagnetic shielding agent to form a modified polypropylene composite material. The method includes hydrothermal reaction of the carbon aerogel powder with the KMnO4 solution to form a carbon aerogel material with MnO2 modified on the surface, and then heating it with the iron salt solution to load FeOOH, thereby improving the electromagnetic shielding performance of the material.

Benefits of technology

It significantly improves the electromagnetic shielding performance of polypropylene materials, with an electromagnetic shielding efficiency of more than 30dB, and is suitable for a variety of electronic equipment and building materials fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215515720000091
    Figure BDA0005215515720000091
Patent Text Reader

Abstract

The invention provides a modified carbon aerogel material, a modified polypropylene composite material and a preparation method thereof, and belongs to the field of high polymer material modification. The preparation method of the modified carbon aerogel material comprises the following steps: adding carbon aerogel powder into a KMnO4 solution, uniformly stirring, carrying out hydrothermal reaction, filtering, washing and drying to obtain a carbon aerogel material of which the surface is modified with MnO2; adding the carbon aerogel material of which the surface is modified with MnO2 into a ferric salt solution, uniformly stirring, heating for reaction, centrifuging, washing and drying to obtain the modified carbon aerogel material of which the surface is loaded with FeOOH. The modified carbon aerogel loaded with FeOOH on the surface is used as an electromagnetic shielding agent to modify the polypropylene material, so that the electromagnetic shielding performance of the polypropylene material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a modified carbon aerogel material, a modified polypropylene composite material with electromagnetic shielding function and a preparation method thereof. Background Art

[0002] As a thermoplastic resin, polypropylene (PP) is widely used in many fields due to its excellent physical and chemical properties. Polypropylene is easy to process and can be formed by injection molding, extrusion, blow molding and other methods. Polypropylene has good toughness and rigidity, good tensile strength and impact resistance, and a high fatigue life.

[0003] With the expansion of polypropylene applications and the high demand for customer products, the development of polymer-based composite materials such as antistatic and electromagnetic shielding has received great attention and extensive research. At present, antistatic additives have been added to PP to achieve the effect of reducing or eliminating static electricity; or by adding conductive agents to improve the conductivity of the material, so as to effectively conduct static charges to the ground or evenly distribute them on the surface of the material to avoid static electricity accumulation. If it is used in electronic equipment, communication equipment, medical equipment, building materials, automobiles and other fields, PP also needs to have electromagnetic shielding properties, so that it can reflect part of the electromagnetic waves back into the air to reduce the impact.

[0004] Therefore, it is necessary to study a polypropylene composite material with electromagnetic shielding function to expand its further application. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a modified carbon aerogel material, a modified polypropylene composite material with electromagnetic shielding function and a preparation method thereof, so as to improve the electromagnetic shielding performance of polypropylene.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a modified carbon aerogel material, which comprises the following steps:

[0008] S1. Adding carbon aerogel powder into KMnO4 solution, stirring evenly and then performing hydrothermal reaction, filtering, washing and drying to obtain carbon aerogel material with surface modified with MnO2;

[0009] S2. Add the carbon aerogel material with surface modification of MnO2 into the iron salt solution, stir evenly and heat to react, and obtain the modified carbon aerogel material with surface loading of FeOOH through centrifugation, washing and drying.

[0010] In a further embodiment, in step S1, the mass ratio of the carbon aerogel powder to KMnO4 is 3-6:200-300;

[0011] The temperature of the hydrothermal reaction is 150-180° C. and the time is 10-15 hours.

[0012] In a further embodiment, in step S2, the iron salt solution is obtained by dissolving the iron salt in an ethylene glycol aqueous solution, wherein the volume ratio of deionized water to ethylene glycol in the ethylene glycol aqueous solution is 5-7:1;

[0013] The iron salt is ferric sulfate, ferric chloride or ferric nitrate.

[0014] In a further embodiment, in step S2, the mass ratio of the carbon aerogel material with surface modified with MnO2 to the iron salt is 20-40:60-80.

[0015] In a further embodiment, in step S2, the heating reaction is performed by placing the reactor in an oven and reacting at 100-150° C. for 2-5 hours.

[0016] The second object of the present invention is to provide a modified carbon aerogel material prepared by the above preparation method.

[0017] The third invention object of the present invention is to provide a modified polypropylene composite material, which is prepared from the following components in parts by weight:

[0018] Polypropylene 95.8-98.3 parts,

[0019] 1-3 parts of electromagnetic shielding agent,

[0020] Antioxidant 0.3-0.6 parts,

[0021] Dispersant 0.4-0.6 parts,

[0022] The electromagnetic shielding agent is the modified carbon aerogel material mentioned above.

[0023] In a further embodiment, the polypropylene is at least one of homopolypropylene and copolymer polypropylene.

[0024] In a further embodiment, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant;

[0025] The dispersant is any one of calcium stearate, zinc stearate, erucic acid amide or macromolecular silicone.

[0026] The fourth invention objective of the present invention is to provide a method for preparing the above-mentioned polypropylene composite material, which comprises the following steps: after uniformly mixing polypropylene, modified carbon aerogel material, antioxidant and dispersant, adding them into a twin-screw extruder, and performing melt mixing and extrusion granulation to obtain a modified polypropylene composite material.

[0027] The temperature of the twin-screw extruder from the feeding section to the die head is 80-100°C, 180-190, 180-190°C, 190-210°C, 190-210°C, 210-220°C, 190-210°C, 190-210°C, 190-200°C, the screw speed is 420r / min, and the screw length-diameter ratio is 48:1.

[0028] The modified carbon aerogel material prepared by the present invention uses carbon aerogel as raw material, which is a porous, lightweight, high specific surface area three-dimensional (3D) network structure nano carbon material; and it is easy to be evenly dispersed in the matrix through shearing in the screw, and is less likely to agglomerate than other carbon materials. Carbon aerogel can provide a rich surface and pore structure, which is convenient for subsequent surface modification and loading processes.

[0029] The present invention reacts potassium permanganate (KMnO4) with carbon aerogel, and KMnO4 is reduced to MnO2 and deposited on the surface of carbon aerogel to form a carbon aerogel material with surface modification of MnO2. Then it reacts with an iron source to generate FeOOH and load it on the surface of carbon aerogel. The one-dimensional structure of FeOOH nanorods has excellent magnetic properties, negative magnetization and electromagnetic absorption function.

[0030] Therefore, the present invention uses the modified carbon aerogel loaded with FeOOH on the surface as an electromagnetic shielding agent to modify the polypropylene material, thereby significantly improving the electromagnetic shielding performance of the polypropylene material. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0033] The raw materials used in the following examples are as follows:

[0034] Polypropylene uses PP YPJ1215C (Yangzi Petrochemical), PP EP300M (CNOOC Shell), and PP 6012 (Sinopec);

[0035] The hindered phenol antioxidant used was antioxidant 1010 (BASF);

[0036] The phosphite antioxidant used was antioxidant 168 (BASF);

[0037] Carbon aerogel powder, KMnO4, FeSO4·7H2O, FeCl2, FeNO3, etc. are all existing commercially available products.

[0038] Embodiment 1:

[0039] 97.1 parts of PP YPJ1215C, 2 parts of modified carbon aerogel material, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.5 parts of calcium stearate were mixed evenly, added to a twin-screw extruder, and subjected to melt mixing, extrusion and granulation to obtain a modified polypropylene composite material.

[0040] The temperatures of the twin-screw extruder from the feeding section to the die are: 90°C, 180, 180°C, 190°C, 190°C, 210°C, 210°C, 210°C, 200°C, the screw speed is 420r / min, and the screw length-to-diameter ratio is 48:1.

[0041] The preparation process of the modified carbon aerogel material is as follows:

[0042] S1. Dissolve 0.15 g KMnO4 in 70 mL deionized water, add 4 mg carbon aerogel powder to the above solution, and stir mechanically for 40 min to obtain a mixed solution;

[0043] S2, introducing the mixed solution into a Teflon high pressure reactor, and subjecting it to hydrothermal reaction at 160°C for 12 hours;

[0044] S3, cooling to room temperature, filtering the solid reactant, washing it with anhydrous ethanol for 4 times, and drying it in an oven at 70°C for 30 minutes to obtain a carbon aerogel material with surface modified with MnO2;

[0045] S4, dissolve 70 mg of FeSO4·7H2O in 70 mL of ethylene glycol aqueous solution (wherein the volume ratio of deionized water to ethylene glycol is 6:1);

[0046] S5, adding 30 mg of the carbon aerogel material with surface modification of MnO2 prepared in step S3 to the solution in S4, and stirring for 50 min;

[0047] S6, transferring the stirred solution to a Teflon reactor, placing it in an oven, and reacting it at 120° C. for 3 hours;

[0048] S7, centrifuging the solid product of the reaction, washing it twice with deionized water and anhydrous ethanol respectively, and drying it at 70° C. for 50 min. Thus, a modified carbon aerogel material with FeOOH loaded on the surface is obtained.

[0049] Embodiment 2:

[0050] 96.1 parts of PP EP300M, 3 parts of modified carbon aerogel material, 0.2 parts of antioxidant 1010, 1680.3 parts of sub-antioxidant, and 0.4 parts of zinc stearate were mixed evenly, added to a twin-screw extruder, melt-mixed, extruded, and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0051] The preparation process of modified carbon aerogel material is as follows:

[0052] S1. Dissolve 0.25 g KMnO4 in 70 mL deionized water, and then add 4 mg carbon aerogel powder to the above solution; mechanically stir for 50 min to obtain a mixed solution;

[0053] S2. The mixed solution was introduced into a Teflon autoclave and subjected to a hydrothermal reaction at 170°C for 12 hours;

[0054] S3. Cool to room temperature, filter the solid reactant, wash it with anhydrous ethanol 5 times, and dry it in an oven at 60 ° C for 50 min to obtain a carbon aerogel material with surface modified with MnO2;

[0055] S4. Dissolve 65 mg of FeSO4·7H2O in 70 mL of ethylene glycol aqueous solution (volume ratio of deionized water:ethylene glycol = 5:1);

[0056] S5. 35 mg of the surface-modified MnO2 carbon aerogel material prepared in step S3 was added to the above S4 solution and stirred for 40 min;

[0057] S6. The stirred solution was transferred to a Teflon reactor, placed in an oven, and reacted at 120°C for 4 hours;

[0058] S7. The solid product is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, and then dried at 75° C. for 40 min. Thus, a carbon aerogel material with FeOOH loaded on the surface is obtained.

[0059] Embodiment 3:

[0060] 97.6 parts of PP 6012, 1.5 parts of modified carbon aerogel material, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.5 parts of erucamide were mixed evenly, added to a twin-screw extruder, and melt-mixed, extruded, and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0061] The preparation process of modified carbon aerogel material is as follows:

[0062] S1. Dissolve 0.3 g KMnO4 in 70 mL deionized water, and then add 4 mg carbon aerogel powder to the above solution; mechanically stir for 40 min to obtain a mixed solution;

[0063] S2. The mixed solution was introduced into a Teflon autoclave and subjected to hydrothermal reaction at 160°C for 12 hours;

[0064] S3. Cool to room temperature, filter the solid reactant, wash it with anhydrous ethanol 5 times, and dry it in an oven at 60°C for 40 minutes to obtain a carbon aerogel material with surface modified with MnO2;

[0065] S4. Dissolve 65 mg FeCl2 in 70 mL of ethylene glycol aqueous solution (volume ratio of deionized water: ethylene glycol = 7:1);

[0066] S5. 35 mg of the surface-modified MnO2 carbon aerogel material prepared in step S3 was added to the above S4 solution and stirred for 40 min;

[0067] S6. The stirred solution was transferred to a Teflon reactor, placed in an oven, and reacted at 140 ° C for 3 hours;

[0068] S7. The solid product is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, and then dried at 65° C. for 30 min. A carbon aerogel material with FeOOH loaded on the surface is obtained.

[0069] Embodiment 4:

[0070] 98.3 parts of PP YPJ1215C, 1 part of modified carbon aerogel material, 0.1 parts of antioxidant 1010, 0.2 parts of antioxidant 168, and 0.4 parts of macromolecular silicone E525 were uniformly mixed, melt-mixed, extruded, and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0071] The preparation process of modified carbon aerogel material is as follows:

[0072] S1. Dissolve 0.1 g KMnO4 in 70 mL deionized water, and then add 3 mg carbon aerogel powder to the above solution; after mechanical stirring for 30 min, a mixed solution is obtained;

[0073] S2. The mixed solution was introduced into a Teflon autoclave and subjected to hydrothermal reaction at 150°C for 12 hours;

[0074] S3. Cool to room temperature, filter the solid reactant, wash it three times with anhydrous ethanol, and dry it in an oven at 50°C for 20 minutes to obtain a carbon aerogel material with surface modified with MnO2;

[0075] S4. Dissolve 60 mg FeNO3 in 70 mL of ethylene glycol aqueous solution (volume ratio of deionized water: ethylene glycol = 5:1);

[0076] S5. 20 mg of the surface-modified MnO2 carbon aerogel material prepared in step S3 was added to the above S4 solution and stirred for 30 min;

[0077] S6. The stirred solution was transferred to a Teflon reactor, placed in an oven, and reacted at 100 ° C for 2 hours;

[0078] S7. The solid product is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, and then dried at 60° C. for 30 min. A carbon aerogel material with FeOOH loaded on the surface is obtained.

[0079] Embodiment 5:

[0080] 95.8 parts of PP EP300M, 3 parts of modified carbon aerogel material, 0.3 parts of antioxidant 1010, 0.3 parts of antioxidant 168 and 0.6 parts of calcium stearate were uniformly mixed, melt-mixed, extruded and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0081] The preparation process of modified carbon aerogel material is as follows:

[0082] S1. Dissolve 0.2 g KMnO4 in 70 mL deionized water, and then add 6 mg carbon aerogel powder to the above solution; mechanically stir for 60 min to obtain a mixed solution;

[0083] S2. The mixed solution was introduced into a Teflon autoclave and subjected to hydrothermal reaction at 180°C for 12 hours;

[0084] S3. Cool to room temperature, filter the solid reactant, wash it with anhydrous ethanol for 3-5 times, and dry it in an oven at 80 ° C for 60 min to obtain a carbon aerogel material with surface modified MnO2;

[0085] S4. Dissolve 80 mg of FeSO4·7H2O in 70 mL of ethylene glycol aqueous solution (deionized water:

[0086] The volume ratio of ethylene glycol = 5-7:1);

[0087] S5. 40 mg of the surface-modified MnO2 carbon aerogel material prepared in step S3 was added to the above S4 solution and stirred for 60 min;

[0088] S6. The stirred solution was transferred to a Teflon reactor, placed in an oven, and reacted at 150°C for 5 hours.

[0089] S7. The solid product is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, and then dried at 80° C. for 60 min. A carbon aerogel material with FeOOH loaded on the surface is obtained.

[0090] Comparative Example 1:

[0091] 97.1 parts of PP YPJ1215C, 2 parts of carbon aerogel powder, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.5 parts of calcium stearate were uniformly mixed, melt-mixed, extruded and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0092] Comparative Example 2:

[0093] 97.1 parts of PP YPJ1215C, 2 parts of carbon nanotubes, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.5 parts of calcium stearate were uniformly mixed, melt-mixed, extruded and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0094] Comparative Example 3:

[0095] 97.1 parts of PP YPJ1215C, 2 parts of conductive carbon black, 0.2 parts of antioxidant 1010, 0.2 parts of antioxidant 168 and 0.5 parts of calcium stearate were uniformly mixed, melt-mixed, extruded and granulated to obtain a modified polypropylene composite material. The parameters of the twin-screw extruder were the same as those in Example 1.

[0096] The modified polypropylene materials prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were made into specimens and cut into test specimens with a size of 23 mm*10 mm*2 mm. The electromagnetic shielding performance was tested, as shown in the following table.

[0097] The specific test method is to use the waveguide method and the test frequency is 8.2-12.4GHz; specifically, use a PX16 power meter connected to a 10x coaxial low-power probe to first measure the input power, then cover the material on the flange port and then measure the output power, and finally obtain the electromagnetic shielding related parameters.

[0098]

[0099] It can be seen from the above table that the modified polypropylene composite materials prepared in Examples 1-5 of the present invention have excellent electromagnetic shielding performance, and the electromagnetic shielding effectiveness thereof reaches above 30 dB.

[0100] By comparing Example 1 with Comparative Examples 1-3, it is found that although equal amounts of carbon aerogel powder, carbon nanotubes, conductive carbon black and other materials are added to Comparative Examples 1-3, the electromagnetic shielding performance of the modified polypropylene composite material is significantly lower than that of Example 1, and its electromagnetic shielding effect is only 15.8-20.1dB.

[0101] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a modified carbon aerogel material, characterized in that: The following steps are involved: S1. Adding carbon aerogel powder into KMnO4 solution, stirring evenly and then performing hydrothermal reaction, filtering, washing and drying to obtain carbon aerogel material with surface modified with MnO2; S2. Add the carbon aerogel material with surface modification of MnO2 into the iron salt solution, stir evenly and heat to react, and obtain the modified carbon aerogel material with surface loading of FeOOH through centrifugation, washing and drying.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the carbon aerogel powder to KMnO4 is 3-6:100-300; The temperature of the hydrothermal reaction is 150-180° C. and the time is 10-15 hours.

3. The preparation method according to claim 1, characterized in that: In step S2, the iron salt solution is prepared by dissolving the iron salt in an ethylene glycol aqueous solution, wherein the volume ratio of deionized water to ethylene glycol in the ethylene glycol aqueous solution is 5-7:1; The iron salt is ferric sulfate, ferric chloride or ferric nitrate.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the carbon aerogel material with surface modified with MnO2 to the iron salt is 20-40:60-80.

5. The preparation method according to claim 1, characterized in that: In step S2, the heating reaction is performed by placing the reactor in an oven and reacting at 100-150° C. for 2-5 hours.

6. The modified carbon aerogel material obtained by the preparation method according to any one of claims 1 to 5.

7. A modified polypropylene composite material, characterized in that: It is prepared from the following components in parts by weight: Polypropylene 95.8-98.3 parts, 1-3 parts of electromagnetic shielding agent, Antioxidant 0.3-0.6 parts, Dispersant 0.4-0.6 parts, The electromagnetic shielding agent is the modified carbon aerogel material as claimed in claim 6.

8. The polypropylene composite material according to claim 7, characterized in that: The polypropylene is at least one of homopolypropylene and copolymer polypropylene.

9. The polypropylene composite material according to claim 7, characterized in that: The antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant; The dispersant is any one of calcium stearate, zinc stearate, erucic acid amide or macromolecular silicone.

10. The method for preparing the polypropylene composite material according to any one of claims 7 to 9, characterized in that: The method comprises the following steps: uniformly mixing polypropylene, modified carbon aerogel material, antioxidant and dispersant, adding the mixture into a twin-screw extruder, and performing melt mixing and extrusion granulation to obtain a modified polypropylene composite material.